Barriers to Law Enforcement Responsive to the Interests of Victims: A Study on the Practice of Justice for Violent Crimes in the Jurisdiction of Class IA Kupang District Court - Fallo , Debby F Ng; Amalo, Heryanto; Dima , Adrianus Djara (Journal of Ecohumanism, 2024)
Objectives: The aim is to identify the barriers to the enforcement of laws against violent crimes that are responsive to the interests of victims of violent crimes. Methods: This research method falls within the specification of empirical legal research/sociological-juridical studies because it is viewed from the perspective of the legal function to protect societal interests. For primary data collection, field research (field interview) was conducted, using a questionnaire as an interview guide, and document study was carried out using a document form as a tool. The collected data were processed procedurally following the processing steps: editing, coding, and tabulation. They were then analyzed qualitatively and further elaborated descriptively. Results: The research results have identified the barriers to the enforcement of laws that are responsive to the interests of victims of violent crimes: the factor of criminal sanctions for violent crimes that do not accommodate the interests of victims of violence; the factor of victims' inability to participate in claiming compensation; the factor of law enforcement bias towards legal certainty aspects, disregarding actions for victim recovery; and the factor of the defendant's economic incapacity to compensate the victim.